Hydrodynamic approach to the centrality dependence of di-hadron correlations - Castilho, Wagner M. [UNESP]; Qian, Wei-Liang [UNESP]; Gardim, Fernando G.; Hama, Yogiro; Kodama, Takeshi (Amer Physical Soc, 2017)
Measurements of di-hadron azimuthal correlations at different centralities for Au + Au collisions at 200A GeV were reported by the PHENIX Collaboration. The data were presented for different ranges of transverse momentum. In particular, it was observed that the away-side correlation evolves from a double-to a single-peak structure when the centrality decreases. In this work, we show that these features naturally appear due to an interplay between the centrality-dependent smooth background elliptic flow and the one produced by event-byevent fluctuating peripheral tubes. To compare with the PHENIX data, we also carry out numerical simulations by using a hydrodynamical code NEXSPHERIO, and calculate the correlations by both cumulant and the ZYAM method employed by the PHENIX Collaboration. Our results are in reasonable agreement with the data. A brief discussion on the physical content of the present model and its difference from other viewpoints is also presented.